Neuronal IRE-1 coordinates an organism-wide cold stress response by regulating fat metabolism - Dudkevich, Reut (2023)
Cold affects many aspects of biology, medicine, agriculture, and industry. Here, we identify a conserved endoplasmic reticulum (ER) stress response, distinct from the canonical unfolded protein response, that maintains lipid homeostasis during extreme cold. We establish that the ER stress sensor IRE-1 is critical for resistance to extreme cold and activated by cold temperature. Specifically, neuronal IRE-1 signals through JNK-1 and neuropeptide signaling to regulate lipid composition within the animal. This cold-response pathway can be bypassed by dietary supplementation with unsaturated fatty acids. Altogether, our findings define an ER-centric conserved organism-wide cold stress response, consisting of molecular neuronal sensors, effectors, and signaling moieties, which control adaptation to cold conditions in the organism. Better understanding of the molecular basis of this stress response is crucial for the optimal use of cold conditions on live organisms and manipulation of lipid saturation homeostasis, which is perturbed in human pathologies.